Antimicrobial Peptide Induced-Stress Renders Staphylococcus aureus Susceptible to Toxic Nucleoside Analogs - Rodríguez-Rojas, Alexandro; Nath, Arpita; El Shazely, Baydaa; Santi, Greta; Kim, Joshua Jay; Weise, Christoph; Kuropka, Benno; Rolff, Jens (Frontiers in Immunology, 2020)
Cationic antimicrobial peptides (AMPs) are active immune effectors of multicellular organisms and also considered as new antimicrobial drug candidates. One of the problems encountered when developing AMPs as drugs is the difficulty to reach sufficient killing concentrations under physiological conditions. Here, using pexiganan, a cationic peptide derived from a host defence peptide of the African clawed frog and the first AMP developed into a drug, we studied if sub-lethal effects of AMPs can be harnessed to devise treatment combinations. We studied the pexiganan stress response of Staphylococcus aureus at sub-lethal concentrations using a whole proteomics approach by liquid chromatography coupled with mass spectrometry. Several proteins involved in nucleotide metabolism were elevated, suggesting a metabolic demand. We then show that S. aureus is highly susceptible to antimetabolite nucleoside analogues when exposed to pexiganan, even at sub-inhibitory concentrations. These findings could be used to enhance pexiganan potency while decreasing the risk of resistance emergence, and our findings can likely be extended to other antimicrobial peptides.